Muscle invasive urinary bladder urothelial carcinoma presenting with secondary nephrotic symptoms. Issue 5 (28th June 2021) - Mizusawa, Hiroya; Mimura, Yuji; Utazu, Haruhiko; Maejima, Toshitaka
Abstract : Introduction: Nephrotic syndrome secondary to malignant disease accounts for approximately 10% of cases of nephrotic syndrome in adults. However, urothelial carcinoma of the bladder is a rare cancer, with only four cases reported to date. Case presentation: A 76‐year‐old man presented with chief complaints of edema and anorexia. Laboratory examinations revealed hypoalbuminemia and marked proteinuria, and computed tomography demonstrated multiple bladder tumors. Transurethral resection of the bladder tumors was performed. The pathological diagnosis was urothelial carcinoma with muscular invasion. The patient underwent simple cystectomy and ileal conduit formation, and proteinuria disappeared after 4 weeks. However, urethral recurrence was noted, and he died 35 months after cystectomy. Conclusion: Five cases including ours were clinically reviewed. Nephrotic symptoms improved relatively rapidly after surgery in all cases. In contrast to the poor preoperative general condition, postoperative improvement can be expected, and surgical treatment should, therefore, be considered.